Ekowisata Mangrove Lembar Selatan: Tinjauan Sosial Ekonomi dan Pemanfaatan Ekologis dalam Mendukung Sustainable Circular Economy dan Pembelajaran IPA Kontekstual - Abdul Gani; Ahmad Aris Arifin; Ahmad Fauzi; Muhammad Yustiqvar; Agil Al Idrus; A. Wahab Jufri (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to analyze the ecological utilization of mangroves, examine the socio-economic aspects of the local community, and assess the relationship between these uses, conservation efforts, and the educational potential of the area. The urgency of the research lies in the need to integrate ecological utilization, socio-economic sustainability, and the application of a Sustainable Circular Economy, while simultaneously strengthening the role of mangrove ecotourism areas as sources of contextual science learning. The research employed a descriptive approach with data collected through structured in-depth interviews and questionnaires administered to 10 respondents. Data were analyzed using a mixed method, consisting of qualitative descriptive analysis for interview results and quantitative descriptive analysis for questionnaire data. The findings indicate that mangrove utilization is mainly limited to the collection of dead wood due to local regulations, while the exploitation of fauna (mollusks, crabs, and fish) is more dominant as a source of income. Community participation in conservation is relatively high, but knowledge regarding the medicinal benefits of mangroves remains low. These results highlight the need to strengthen sustainable, circular-economy-based utilization and to optimize the area as a source of contextual science learning.